Contribuição da vegetação de entorno na diversidade de inimigos naturais e no controle conservativo de pragas do cafeeiro - Marques, Kulian Basil Santa Cecília (2021)
Pest control of agricultural crops by their natural enemies is a valuable ecosystem service for agriculture, but little quantified. Understanding how landscape features facilitate or hinder the movement of pests and natural enemies can provide important information on migration to crops and have implications for the management of arthropod-mediated ecosystem services. It is known that there is an enrichment of natural enemies and more effective biological control where natural vegetation remains on the margins of crops, such as forest fragments, riparian forests or other crops. This work aims to monitor the population fluctuation and parasitism of the coffee berry borer and the coffee leaf miner as well as the action of natural enemies, correlating to climatic factors. Different plots of coffee were sampled, one of coffee in monoculture, and the others with different surrounding vegetation: australian red cedar, pasture and forest fragment. The abundance, richness and diversity of hymenopteran parasitoids was also determined, and the influence of the surrounding vegetation on the composition of the community of these insects in the coffee system was evaluated. In these areas, brocaded fruits were also collected to observe the emergence of parasitoids of the coffee borer. The project was developed in the municipality of Coqueiral-MG, for two years, where field worksheets were used to assess pests and natural enemies, in addition to collecting leaves, fruits and using “pan trap” traps to capture insects. Regarding the parasitoids of the coffee leaf miner, 392 hymenopteran parasitoids were collected, of which 204 were braconids and 190 eulophids and the most abundant species were Stiropius reticulatus, Orgilus niger and Proacrias coffeae. A total of 2042 insects from eight superfamilies, 23 families and 187 morphospecies were collected with the pan trap traps and the results showed a greater abundance of parasitoids, related to the biological control of coffee pests, in the coffee treatment with vegetation surrounding Australian red cedar. Prorops nasuta parasitoid were found in brocade fruits evaluated in the treatments. The coffee leaf miner did not cause economic damage, but the infestation of the coffee borer reached the level of economic damage in conventional coffee in monoculture and also with vegetation surrounding Australian red cedar. Obtaining this information broadened the knowledge of the ecological benefits related to the vegetation surrounding coffee plantations, the population dynamics of pests and natural enemies associated with coffee, and the distribution of diversity and abundance of parasitoids, thus providing bases for the recommendation of biological control by conservation in coffee growing in the south of Minas Gerais.